Inhibition of gene expression by anti-sense C-5 propyne oligonucleotides detected by a reporter enzyme. - Hamel, Y (1999)
Using a reporter plasmid containing the luciferase gene under the control of the insulin-like growth factor 1 (IGF-1) promoter region [including its 5' untranslated region (UTR)], we demonstrate that a 17-mer oligophosphorothioate containing C-5 propyne pyrimidines is able to inhibit luciferase gene expression in the nanomolar concentration range when the anti-sense oligonucleotide is targeted either to a coding sequence in the luciferase gene or to the 5' UTR of the gene for IGF-1. Inhibition was obtained independently of whether the plasmid and the anti-sense oligonucleotide were co-transfected or transfected separately into hepatocarcinoma cells. However, the efficiency of inhibition by the anti-sense oligonucleotides was 10-fold greater in the first case. The unmodified oligophosphorothioate targeted to the 5' UTR of IGF-1 did not inhibit luciferase gene expression at a 100-fold higher concentration unless its length was increased from 17 to 21 nt, in which case an inhibition of gene expression was obtained and an IC50 of 200 nM was observed.